2009
DOI: 10.2174/156652409788167113
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Tumor Microenvironment and Cancer Cell Differentiation

Abstract: Hypoxia or oxygen deficiency is a salient feature of solid tumors. Hypoxic tumors are often resistant to conventional cancer therapies, and tumor hypoxia correlates with advanced stages of malignancy. Hypoxic tumors appear to be poorly differentiated. Increasing evidence suggests that hypoxia has the potential to inhibit tumor cell differentiation and thus plays a direct role in the maintenance of cancer stem cells. Studies have also shown that hypoxia blocks differentiation of mesenchymal stem/progenitor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 145 publications
4
116
0
1
Order By: Relevance
“…Interestingly, both CTGF and Igfbp5 have been independently found to inhibit osteoblast maturation and differentiation [63,64] while MGP is an ECM protein that has been shown to inhibit mineralization and apoptosis of chondrocytes [65]. These findings suggest that interactions between leukemia and the BM stroma induce changes towards an undifferentiated state of the tumor microenvironment that could contribute to disease progression and chemotherapy resistance [66]. Furthermore, our findings indicate upregulation of genes related to complement (C4A, C4B, and SERPING1) in BM-MSC exposed to leukemia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both CTGF and Igfbp5 have been independently found to inhibit osteoblast maturation and differentiation [63,64] while MGP is an ECM protein that has been shown to inhibit mineralization and apoptosis of chondrocytes [65]. These findings suggest that interactions between leukemia and the BM stroma induce changes towards an undifferentiated state of the tumor microenvironment that could contribute to disease progression and chemotherapy resistance [66]. Furthermore, our findings indicate upregulation of genes related to complement (C4A, C4B, and SERPING1) in BM-MSC exposed to leukemia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The lowered blood supply indicates a lower number of red blood cells being able to reach the tumour cells resulting in decreased oxygen delivery [52]. Moreover, hypoxic tumours have a greater ability to resist standard treatments and the tumour cells are often in a less differentiated or more stem cell-like state [53]. Emerging evidence has shown that exosomes are key membrane vesicles secreted by most cell types under hypoxia.…”
Section: Exosomes the Tumour Microenvironment And Hypoxiamentioning
confidence: 99%
“…Hypoxia in the head and neck squamous cell carcinoma tumor microenvironment: mechanisms, effects, diagnostic methods and clinical significance When compared with the healthy tissues around many solid tumor microenvironments, such as breast, brain, cervix, prostate, rectum, and head and neck cancers, a significant level of hypoxia has been demonstrated (38). Heterogeneously distributed hypoxic areas at different levels were found in the microenvironment of 50-60% of locally advanced tumors (35).…”
Section: Hypoxia In the Tumor Microenvironmentmentioning
confidence: 99%